Hemorrhagic Stroke in a Dog with Anaplastic Carcinoma of the Mammary Gland - de Cecco, Bianca Santana; Lorenzett, Mariana Paula; Vargas, Thainã Piccolo; Wronski, Júlia Gabriela; Düster, Marcia; Siqueira, Franciele Maboni; Pavarini, Saulo Petinatti; Driemeier, David (Acta Scientiae Veterinariae, 2019)
Background: anaplastic carcinoma of the mammary gland is considered a highly invasive and malignant neoplasia, which usually leads to neoplastic thrombosis and epidermal ulceration due to invasiveness of lymphatic vessels by tumor emboli. Loss of epidermal barrier predisposes to secondary bacterial infection, mainly by commensal bacteria of the skin, and septicemia can be observed in cases of systemic dissemination. Neoplastic emboli and septic thrombi can lead to vascular obstruction, which can predispose to infarction in multiple organs. The aim of this case report is to describe a case of hemorrhagic stroke in a dog with anaplastic carcinoma of the mammary gland. Case: a 12-year-old, mixed breed, female spayed canine presented with mammary tumor with plaque formation, associated with skin ulceration which extended to the medial region of pelvic limbs. The animal also displayed neurologic clinical signs characterized by stupor, opisthotonos and apathy. Due to poor prognosis, the canine was euthanized and submitted to necropsy. During external examination, the animal was in a good body condition, had moderately pale mucosae, and it was noted a nodular plaque in the abdominal ventral area extending from thoracic to inguinal mammary gland. The mass was firm and white, extensively ulcerated, and extending from the thoracic to inguinal mammary gland. There was a well circumscribed area of infarction in the spleen and kidney. In the cerebral cortex it was observed an extensive area of hemorrhage with adhered blood clot from frontal to temporal lobe. There were multiple well circumscribed, firm, and white areas in the myocardium. Histologically, the neoplastic proliferation was composed by epithelial cells with high pleomorphism, features of malignancy, and no delimitations, leading to the diagnosis of anaplastic carcinoma of the mammary gland. Admixed with tumor cells there were multiple areas of hemorrhage, necrosis and thrombosis. In the cerebral cortex there was a focally extensive area of hemorrhage, multifocal thrombosis, abundant amount of gitter cells, and moderate perivascular inflammatory infiltrate of lymphocytes. There was neoplastic infiltrate in the bladder, adrenal glands, and lungs. There were multiple areas of necrosis and thrombosis in spleen and heart. Bacterial examination was performed in fragments of cerebral cortex and kidney, and Staphylococcus pseudintermedius was isolated. Discussion: anaplastic carcinoma of the mammary gland has an epithelial origin and is considered the most malignant neoplasm with worst prognosis due to its characteristic of high cellular pleomorphism and the ability of invasiveness of vessels and adjacent tissues. Therapeutic options are scarce and palliative, and surgical removal is not indicated. Dermal ulceration usually is infected by opportunistic bacteria that can lead to inflammation and pain, and treatment in these cases is focused on pain management with analgesics. The bacterial infection can evolve to septicemia with decrease of endogenous anticoagulants and consequent blood hypercoagulability. Moreover, studies demonstrate the higher risk of clotting abnormalities when associated to progression of mammary carcinomas, which includes anaplastic carcinoma of the mammary gland. In this study, two causes which may have led to thromboembolism and cerebral hemorrhage are discussed: septicemia after invasion of lymphatic vessels by the anaplastic carcinoma or hypercoagulability caused by the systemic neoplasia, which could have reduce the blood flow to vessels of the cerebral cortex.